Language Style and Register on “Close the Door Podcast with Vilmei” based on Sociolinguistics View - Loria Sitanggang; Inggrid Sianipar; Erika Sianturi; Rachel Silalahi; Tiarma Intan Marpaung (YAYASAN PADHANG MANAH SIBYAN, 2026)
This research examines variations in language style and the application of formal and informal registers in social media communication, with a particular emphasis on YouTube podcast content featuring public figures within the young adult demographic. The study centers on a widely discussed viral case involving Livy Renata, Vilmei, and Willie, which generated controversy as a result of contrasting interpretations of informal language use in addressing private matters in a public digital space. Adopting a qualitative descriptive methodology, this study applies a sociolinguistic discourse analysis approach. Data were collected from YouTube video transcriptions, relevant conversational excerpts, and the broader social context surrounding the conflict. The results reveal that the prevalent use of informal registers including slang expressions, Indonesian-English code-switching, and relaxed conversational patterns played a significant role in creating misunderstandings and eliciting emotional responses from the individuals involved. Furthermore, a noticeable shift toward a more formal and reflective register emerged when the issue was addressed in a different podcast setting. Overall, the findings highlight that register selection in social media discourse significantly influences public interpretation and may intensify social conflict, especially among young adults.